OBTAIN E: outcome benefits of tranexamic acid in hip arthroplasty with enoxaparin: a randomised double-blinded controlled trial. Issue 3 (May 2019) - Fraval, Andrew; Duncan, Sam; Murray, Theresa; Duggan, Jeremy; Tirosh, Oren; Tran, Phong
Background: We examined the blood conserving effect of tranexamic acid in total hip arthroplasty using the direct anterior approach with enoxaparin as deep vein thrombosis (DVT) chemoprophylaxis, and whether this translates to an effect on functional outcomes in the perioperative period. We also compare the effect of aspirin and enoxaparin as DVT chemoprophylactic agents. Methods: We conducted a single-centre randomised, double-blinded, placebo-controlled trial. 105 patients were randomised to receive either tranexamic acid or an equivalent volume of normal saline with enoxaparin used as DVT chemoprophylaxis. The primary outcome measure was thigh swelling. Blood loss and the incidence of blood transfusions was also recorded. Secondary outcome measures including postoperative functional scores and mobility, pain scores and length of stay. We also compared and pooled the results of a previous study with the same study intervention methodology which used aspirin as DVT chemoprophylaxis instead of enoxaparin. Results: There were no statistically significant differences between the primary outcome of thigh swelling. There was significantly less intraoperative blood loss observed in the tranexamic acid (TXA) group (0.510 L, SD 0.210) compared with the control group (0.698, SD 0.301) ( p < 0.001). The estimated blood loss was also significantly less in the TXA group (1.130 L, SD 0.311) compared with the control group (1.48 L, SD 0.510) ( p < 0.001). Pooled data of both consecutive trials showed there was a statistically significant reduction in length of stay for those that received TXA (3.72 days, SD 0.83 versus 4.24 days, SD 0.97, p < 0.001). There was also a statistically significant increased risk of a transfusion in the control group as compared those that received TXA (OR 5.5, 1.188 to 25.449, p = 0.029). There was no difference in blood loss between DVT chemoprophylactic agents. Interpretation: TXA is an effective agent in reducing blood loss in THR using the anterior approach and was not affected by choice of DVT chemoprophylaxis. Patients who received TXA had fewer transfusions and a reduction in their length of stay. The blood conserving effect of TXA was not associated with improved postoperative recovery across the measures of pain and mobility. Clinical trials registration: ANZCTR number: ACTRN12616000606482.